pengaruh kecerdasan emosional,lingkungan sekolah,media pembelajaran,dan lingkungan keluarga terhadap hasil belajar melalui variabel disiplin belajar siswa kelas X fase E pada mata pelajaran ekonomi di sman 13 padang - Nurhasana, Afdhalita; Lovelly Dwinda Dahen; Dina Amaluis (Global Action and Education for Society, 2026)
This study aims to determine: the influence of emotional intelligence, school environment, learning media, family environment and learning discipline on the learning outcomes of class X students in Phase E Economics Subjects at SMA N 13 Padang. This type of research is associative. The population in this study were class X students in Economics Subjects at SMAN 13 Padang. The sampling technique used the Proportional Random Sampling technique. Based on learning outcomes. The results of this study indicate the influence of emotional intelligence on discipline with a significant value of 0.886> t count 144, school environment on discipline with a significant value of 0.019> t count 2.384, learning media on learning discipline with a significant value of 0.024> t count 2.299, family environment on learning discipline with a significant value of 0.011> t count 2.576, emotional intelligence on learning outcomes with a significant value of 0.001> t count 3.994, school environment on learning outcomes with a significant value of 0.000> t-count 3.994, learning media on learning outcomes with a significant value of 0.234> t-count 1.198, family environment on learning outcomes with a significant value of 0.000> t-count 10.091, learning discipline on learning outcomes 0.214> t-count 1.251.